UPAYA PEMERINTAH INDONESIA DALAM MEMINIMALISIR IMPOR PRODUK ELEKTRONIK TIONGKOK SECARA BERLEBIH PASCA KERJA SAMA ASEAN-CHINA FREE TRADE AREA (ACFTA) PERIODE 2018-2021 - Ahmad Bagus Maulanasyah (2023)
Indonesia suffered losses in the electronics sector due to imports of mobile phone products from China which entered easily through the ASEAN-China Free Trade Area agreement during the 2018-2021 year. The concepts, theories, and methods used in this study are the theory of competitive advantage, the concept of free trade agreements, institutional liberalism, and qualitative methods by Creswell using primary and secondary data for data sources and using data analysis techniques in the form of descriptive analysis and interview analysis. In this study, it was concluded that the Government made efforts internally and externally by implementing the Program for Increasing the Use of Domestic Products (P3DN), implementing efforts to use the Indonesian National Standard (SNI), registrationInternational Mobile Equipment Identity (IMEI), implementing the Prohibition and Restriction of Goods (LARTAS), and entering into agreements with foreign electronics companies namely Huawei, Lenovo and ZTE Cooperation to improve the quality of Indonesian mobile phones. The government also plays an important role as a forum for foreign companies that want to build their factories and invest in Indonesian electronic products in order to advance Indonesian technology so that they can compete with other electronic products in the free market around the world, both with fellow ASEAN members and with China itself.